Efektivitas Keberlakuan Fatwa MUI di Indonesia: Studi Komparatif antara Fatwa MUI di tingkat Pusat dan Daerah Tentang Kadar Zakat Fitrah - Rohmah, Nihayatur (Al-Syakhsiyyah: Journal of Law and Family Studies, 2024)
This study aims to evaluate the effectiveness of implementing fatwas issued by the Indonesian Council of Islamic Scholars (Majelis Ulama Indonesia, MUI) concerning zakat fitrah at both central and regional levels. By comparing the influence of MUI’s central and regional fatwas on community practices, this qualitative research utilizes observations and interviews with relevant stakeholders. Survey data collected from various regions across Indonesia were analyzed to identify trends and preferences in the public's adherence to MUI fatwas. The results show that 28% of respondents follow the guidelines from the National Zakat Agency (BAZNAS), 34% adhere to the central MUI fatwa, and 39% comply with regional MUI fatwas. These findings highlight the significant impact of regional-level fatwas on zakat fitrah practices. This study contributes to a deeper understanding of the effectiveness of religious decrees in Indonesia and provides valuable insights for enhancing public awareness and participation in the implementation of zakat fitrah.